Toward Sustainable Tourism in Qatar: Msheireb Downtown Doha as a Case Study - Al-Hammadi, Mariam I. (Frontiers in Sustainable Cities, 2022)
Qatar has developed a strategy of sustainable tourism and development, which focuses on highlighting the spirit of the Qatari identity and heritage. This strategy goes hand in hand together with the line of the Qatar National Vision 2030. Hence, Msheireb Properties, which is a real estate development company and a subsidiary of Qatar Foundation, focuses in developing a sustainable tourism strategy. Thus, Qatari cultural heritage presented in the heart of the post-modern futuristic city of Msheireb through the project of Msheireb Museums that are hosted in four traditional houses. Msheireb Properties renovated the four houses in a sustainable way that aimed to create a dynamic relationship between tourism and cultural heritage. Msheireb Properties preserved models of traditional architecture through the establishment of Msheireb Museums. This article discusses the development of sustainable tourism in Qatar and the preservation of the Qatari cultural heritage and identity through the story of two museums in Msheireb, the Radwani House Museum and the Company House Museum.